"SYNTHESIS, STRUCTURAL STUDY (GEOMETRIC ISOMERS) AND ANTIPARASITIC ACTIVITY OF THIOSEMICARBAZONES." - GLINMA, BIENVENU; AGNIMONHAN, Finagnon H.; AHOUSSI, AKANNI LÉON; KPOVIESSI DOSSOU, SIKA SALOME; POUPAERT, H. Jacques; Quetin-Leclercq, Joëlle; GBAGUIDI, Ahokannou Fernand (My University, 2021)
Geometric isomerism is the phenomenon of organic chemistry characterized by the asymmetry arising from at least two different substituents, linked to two atoms engaged with each other by a double bond. Molecules comprising the C=N double bond in their chain have been studied a lot because of the many properties of this functional unit both in terms of acid-base and redox, and even photochemical properties. Thiosemicarbazones, semicarbazones and their derivatives are the major subgroups of hydrazones (C=N-N-), alongside thioaroylhydrazones ... Here, we have synthesized six thiosemicarbazones from acetophenone (P1-3) and propiophenone (P4-6) with good yields. A structural study of the products based on their IR and 1H and 13C NMR spectra was made. Biological activity of products was evaluated on parasite Trypanosoma brucei brucei. It was remarked that the different structural elements of propiophenone thiosemicarbazones (P4-6) exhibited two chemical shifts in NMR as well as two absorption bands in IR ; they appeared in their spectrum as two isomers cis and trans in the 2:3 ratio while molecules (P1-3) with only a single chemical shift for its elements were present more under the anti configuration, which is more predominant. Several electronic and steric factors contributed to the adoption of this observed arrangement. For all products, thiosemicarbazones (P4-6) with their IC50 ranging from 7 to 210 μM and SI = 1 and 119 for P5 and P6 respectively were more actives and selectives on the parasite than their corresponding (P1-3). Products could open opportunity to the treatment of trypanosomiasis.
Keywords: Synthesis; thiosemicarbazones; isomers cis and trans; selectivity